A double-edged sword: The effects of R&D intensity and capitalization on institutional investment in entrepreneurial firms - Feng, Yuan; Ma, Chenyang; Wang, Yushi; Ma, Jiangshui (Frontiers in Psychology, 2022)
Studies show that research and development (R&D) may not always benefit entrepreneurial firms. This paper focuses on the double-edged effect of R&D activities on attracting institutional investment in entrepreneurial firms. Based on a panel dataset of 700 listed entrepreneurial firms in ChiNext, we document: 1) an inverted-U relationship between R&D intensity and future institutional investment, which we argue is evidence that institutional investors are concerned about R&D overinvestment; 2) an inverted-U relationship between R&D capitalization and future institutional investment, which we argue shows suspicion of the institutional investors towards high R&D capitalization. Furthermore, by splitting institutional investors into venture capitals (VCs) and non-venture capitals (non-VCs), we confirm that VCs have higher acceptance of both R&D intensity and capitalization as VCs have more expertise to alleviate a certain level of risks.